Effect of aerobic dance as therapeutic exercise on blood pressure, fasting blood glucose and body weight among adult female hypertensive patients / Noor Nazurah Nerman - Nerman, Noor Nazurah (Faculty of Sport Science and Recreation, 2016)
The present study conducted to examine the effect of aerobic dance exercise as therapeutic exercise on blood pressure, systolic and diastolic blood pressure, fasting blood glucose and body weight among adult female hypertensive patients. Crossover study design was used for this study. Meanwhile, mixed-design ANOVA statistic was used to describe a comparison of four major components between two groups and two periods of time. A total of 40 adult female hypertensive patients (n=40) from the resident areas at Felda Lok Heng at Kota Tinggi, Johor with aged 52.9 ± 8.34 years old were took part in this study. Intervention group (n=20) was subjected to carry out the effectiveness of aerobic dance to reduce high blood pressure, high blood glucose and ·body weight in 6-week intervention with three times a week, while control group (n=20) was asked to continue their normal daily lifestyle as usual. Assessment for systolic and diastolic blood pressure, fasting blood glucose and body weight were done before and after 6-week. Result shown the scores for systolic blood pressure (p<0.05), diastolic blood pressure (p=0.05), fasting blood glucose (p<0.05) and body weight (p<0.05) between both groups at the end of the study period.